Physical activity profile of women in the urban municipality of Catarman, Northern Samar - Lelix, Ida M.
The study explored the knowledge, perception, and practices on physical activity among the adult women in the urban barangays of Catarman. The specific objectives of the study included description of the activity level of women in the occupational, non-occupational, and transportation domains of physical activity; their knowledge level and perceptions of the benefits of physical activity in the prevention of cardiovascular diseases, and guidelines of physical activity and exercise; description of their perceived barriers to physical activity and exercise; determination of the prevalence of selected risk factors of cardiovascular diseases including hypertension, and obesity (BMI, WHR); and the relationship between physical activity, hypertension, and obesity (BMI, WHR); and recommendation of a health promotion program on physical activity based on the findings of the study. The study utilized a descriptive cross-sectional design with two methods of data gathering: the first, through the use of structured questionnaire, designed for interview and second through an in-depth discussion of issues by a focus group discussion (FGD). The respondents were determined through a two-stage cluster sampling design where five out of the 22 urban barangays were randomly selected. Respondents were located by the number of households in each of the identified barangays. He total respondents were 528 women.